Analysis and implementation of a solar/biogas hybrid system for centralized generation at Qadirpur Ran. (November 2022) - Imran, Muhammad; Rashid, Zeeshan; Amjad, Muhammad; Baloch, Shadi Khan; Mustafa, Adil
Abstract: The face of state administered utility grid is suffering from a severe stress due to the rapidly growing urban communities, population, luxurious lifestyle of residents and eventually their electricity needs. This trend being accelerated at a higher pace during the past decade calls for the incorporation of alternative power sources using renewables in grid-tied or islanding mode of operation so-called microgrid. This paper addresses the technical issues associated with a 132 kV grid dedicated to Qadirpur Ran, a rural district of Pakistan located adjacent to the city of Multan. The existing electrical architecture of the district is simulated using power flow solver which illustrates that the components of the grid undergo high losses, poor voltage profile and low power factor. In addition, the simulation study identifies 20 overloaded transformers and 20 overloaded distributed lines in the existing system. Without altering the network configuration, a solar plant and a biogas plant of 10 MW capacity each along with three additional biogas plants of 5 MW (2 MW, 2 MW, 1 MW) rating which serve as emergency backup during night time are proposed for the district. As a result, the district is isolated from the national grid eliminating complexities associated with grid integration and serving as an electrically autonomous enclave. The updated hybrid system announces appealing features in a broad spectrum of electrical power framework compared to the existing quantities providing exquisite solutions to the prevailing issues. Furthermore, the cost of all-renewable powered off-grid system is calculated taking into account contributed supplementary components to estimate the total payback period of 9.75 years.